Re-Examing the Indonesian Language Pragmatic Abilities of Students Majoring in Hospitality as a Basis for Exploring Students' Intercultural Abilities in Japanese - Devita Widyaningtyas Yogyanti; Dwi Iswahyuni; Angela Bayu Pertama Sari (Universitas Cokroaminoto Palopo, 2023)
This research focuses on the intercultural competence of Japanese language students majoring in hospitality at three vocational schools in Yogyakarta. To be able to find out students' intercultural competence, a contrastive analysis method is used regarding politeness strategies in the context of greeting guests, asking the guest's name, asking for general information, rejecting the guest's wishes, asking for something from the guest and confirming. There are three things compared in this research, namely, politeness strategies in Indonesian sentences made by students, politeness strategies in Japanese sentences from native Japanese and the suitability of Indonesian translations into Japanese made by students. Brown and Levenson's face-threatening act (FTA) management theory was used as the theoretical basis for this research. The research results show that politeness strategies in the mother tongue do influence how students translate. In general, there are many similarities in strategies between Indonesian and Japanese regarding politeness strategies in the hospitality context. The similarity of these strategies will make it easier for students to achieve intercultural competence. It is just that a lack of linguistic ability still causes pragmalingustic failure and sociopragmatic failure. Furthermore, the difference in strategy is that the use of bald on record in Indonesian produces a bald on record translation in Japanese, which causes sociopragmatic failure.